CFD simulation of local exhaust ventilation for aviation fire-test lab - S H Al-Ammari, Aiman; S M Altarazi, Yazan; Rahim Abu Talib, Abd.; Nadiir Bheekhun, M (International Journal of Engineering and Technology, 2018)
Excellent indoor air quality in an enclosed area has always become a major safety aspect in designing a building. Issues with regards to circulation of air and exhaust system must be first resolved before the said building can be used for any purposes. The goal of this study is to identify ways to improve air quality in the aviation fire test room at the Propulsion Laboratory that is located in Universiti Putra Malaysia (UPM), Selangor, Malaysia. A computational fluid dynamics (CFD) method was employed to predict the air contaminant inside the lab. When performing the activities, the indoor air quality have to be ensure circulated and ventilated in the lab. Using a mechanical fans and natural ventilation are a traditional method to provide indoor air quality into the propulsion. Whereby, this method may not be enough to provide the required indoor air quality for specific aviation fire-test setup. Such labs may suffer from increasing air contaminant based on the improper and irregular air distribution. A grid independent test (GIT) was done to reduce the effects of meshing on the results was carried out to estimate the discretization error. Computational fluid dynamic (CFD) method was carried out to identify a suitable ventilation system that would result in the greatest improvement in the indoor air quality (IAQ) inside the lab. The results of using the CFD simulation show that installing Local Exhaust Ventilation (LEV) at the lab could significantly improve the IAQ inside the lab. The airflow increase by 84% and the CO, CO2 and NO reduce by 84%, 89 and 81%, respectively. Improvement of the IAQ by increasing the airflow and reducing in the air CO, CO2, and NO, which can be considered as very significant achievement.Â Â Â